Sexual equality : writings - Mill, John Stuart, 1806-1873 (desLibris. Books collection., 1994)
All the significant ideas in nineteenth-century English feminism can be found in the prose and thought of John Stuart Mill and in those of the two women central to his life: Harriet Taylor, who married him in 1851, and her daughter, Helen Taylor. Together they produced some of the most powerful and influential writings ever penned to promote women's equality, and it was to this family that the Victorian women's movement in England came to look for leadership, guidance, and money. In this volume, Ann Robson and John Robson bring together the writings and speeches from these three seminal thinkers on the subject of sexual equality. Some of these pieces have not been available in published form for more than a century. They cover such topics as love, sex, marriage, children, property, domestic relations, divorce, and suffrage. Sexual Equality is a necessary tool for understanding the development of ideas on women's issues in the Mill household. These ideas influenced thinking on sexual equality far beyond England and far past the Victorian period.